The Role of Multimedia in Religious Learning for Students with Disabilities in The Inclusive System (Case Study: Lancang Kuning University) - Nijal, Lasri; Zamzami, Z; Siswanto, Didik; Febriadi, Bayu (IJISTECH (International Journal of Information System and Technology), 2024)
Lancang Kuning University (Unilak) has committed to the success of the disability-friendly Inclusive Indonesia movement program, by providing opportunities for students with disabilities to study at Lancang Kuning University. Delivering Islamic religious lecture material in inclusion classes requires special attention. So by using qualitative research methods, based on direct observation in the classroom and through journals, guide books and expert information, the use of multimedia is very necessary for inclusive classes. Among the media used for learning Islamic Religious Education are; Two-Dimensional Learning Media such as; powerpoint or slide, whiteboard, module book, three-dimensional learning media such as; Equipment for holding corpses and practicing prayer movements, learning media in the form of applications such as applications that can convert sound into writing. Apart from appropriate learning media and various religion lecturers, they also need to master this multimedia and also need to learn to use sign language for the deaf. For supporting facilities, Unilak has provided all sufficient facilities so that inclusion classes at Unilak run well.